mRNA expression levels of hypoxia-induced and stem cell-associated genes in human glioblastoma - Bache, Matthias; Rot, Swetlana; Kessler, Jacqueline; Guettler, Antje; Wichmann, Henri; Greither, Thomas; Wach, Sven; Taubert, Helge; Soeling, Ariane; Bilkenroth, Udo; Kappler, Matthias; Vordermark, Dirk (Oncology Reports, 2015)
The roles of hypoxia-induced and stem cell-associated genes in the development of malignancy and tumour progression are well known. However, there are a limited number of studies analysing the impact of mRNA expression levels of hypoxia-induced and stem cell-associated genes in the tissues of brain tumours and glioblastoma patients. In this study, tumour tissues from patients with glioblastoma multiforme and tumour adjacent tissues were analysed. We investigated mRNA expression levels of hypoxia-inducible factor-1? (HIF-1?), hypoxia-inducible factor-2? (HIF-2?), carbonic anhydrase 9 (CA9), vascular endothelial growth factor (VEGF), glucose transporter-1 (GLUT-1) and osteopontin (OPN), and stem cell-associated genes survivin, epidermal growth factor receptor (EGFR), human telomerase reverse transcriptase (hTERT), Nanog and octamer binding transcription factor 4 (OCT4) using quantitative real-time polymerase chain reaction (qRT-PCR). Our data revealed higher mRNA expression levels of hypoxia-induced and stem cell-associated genes in tumour tissue than levels in the tumour adjacent tissues in patients with glioblastoma multiforme. A strong positive correlation between the mRNA expression levels of HIF-2?, CA9, VEGF, GLUT-1 and OPN suggests a specific hypoxia-associated profile of mRNA expression in glioblastoma multiforme. Additionally, the results indicate the role of stem-cell-related genes in tumour hypoxia. Kaplan-Maier analysis revealed that high mRNA expression levels of hypoxia-induced markers showed a trend towards shorter overall survival in glioblastoma patients (P=0.061). Our data suggest that mRNA expression levels of hypoxia-induced genes are important tumour markers in patients with glioblastoma multiforme.
EVALuna2:16334